Modelling metastasis in zebrafish unveils regulatory interactions of cancer-associated fibroblasts with circulating tumour cells - Hurtado, Pablo; Martínez-Pena, Inés; Yepes-Rodríguez, Sabrina; Bascoy-Otero, Miguel; Abuín, Carmen; Fernández-Santiago, Cristóbal; Sánchez, Laura; López-López, Rafael; Piñeiro, Roberto (Frontiers in Cell and Developmental Biology, 2023)
The dynamic intercommunication between tumour cells and cells from the microenvironment, such as cancer-associated fibroblast (CAFs), is a key factor driving breast cancer (BC) metastasis. Clusters of circulating tumour cells (CTCs), known to bare a higher efficiency at establishing metastases, are found in the blood of BC patients, often accompanied by CAFs in heterotypic CTC-clusters. Previously we have shown the utility of CTC-clusters models and the zebrafish embryo as a model of metastasis to understand the biology of breast cancer CTC-clusters. In this work, we use the zebrafish embryo to study the interactions between CTCs in homotypic clusters and CTC-CAFs in heterotypic CTC-clusters to identify potential pro-metastatic traits derived from CTC-CAF communication. We found that upon dissemination CAFs seem to exert a pro-survival and pro-proliferative effect on the CTCs, but only when CTCs and CAFs remain joined as cell clusters. Our data indicate that the clustering of CTC and CAF allows the establishment of physical interactions that when maintained over time favour the selection of CTCs with a higher capacity to survive and proliferate upon dissemination. Importantly, this effect seems to be dependent on the survival of disseminated CAFs and was not observed in the presence of normal fibroblasts. Moreover, we show that CAFs can exert regulatory effects on the CTCs without being involved in promoting tumour cell invasion, and these effects are differential based on the BC cell molecular phenotype, and the crosstalk between tumour cells and CAFs, i.e. paracrine or physical interaction. Lastly, we show that the physical communication between BC cells and CAFs leads to the production of soluble factors involved in BC cell survival and proliferation. These findings suggest the existence of a CAF-regulatory effect on CTC survival and proliferation sustained by cell-to-cell contacts and highlight the need to understand the molecular mechanisms that mediate the interaction between the CTCs and CAFs in clusters enhancing the metastatic capacity of CTCs.